Gaya Bahasa dan Makna Puisi Tomino no Jigoku dan Hashigo Karya Saizo Yaso - Jiona Diah Karsani, Putu (Humanis; Vol 21 No 1 (2017), 2017)
The research titled is “Language Style and Meaning of The Poem of Tomino no Jigoku and Hashigo by Saizo Yaso”. The purpose of this research is to determine the use of language style and meaning of this poem. Collected data then analyzed using descriptive analysis methods and techniques. The theories used are rhetoric theory by Seto Kenichi  (2002) and Michael Riffaterre’s Semiotic(1978). Results of the analysis showed that the tomino's poem no Jigoku has 5 kinds of rhetoric that are hyperbole, rhetorical questions, repetition, climax, and allusions. The theme of this poem is suffering. Then in poem of Hashigo there are7 kinds of rhetoric such as personification, synesthesia, oksimiron, implications, repetition, inversion, and allegory. The theme of the poem of  Hashigo is death. The use of rhetoric and semiotics in this poem are to show the meaning of the poem so we can find the true meaning of analyzed poetry. Moreover the use of rhetoric also functioned to beautify the poem.